Immigration, Growth and Unemployment: Panel VAR Evidence from OECD Countries - Ekrame Boubtane; Dramane Coulibaly; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper examines empirically the interaction between immigration and host country economic conditions. We employ panel VAR techniques to use a large annual dataset on 22 OECD countries over the period 1987-2009. The VAR approach allows to addresses the endogeneity problem by allowing the endogenous interaction between the variables in the system. Our results provide evidence of migration contribution to host economic prosperity (positive impact on GDP per capita and negative impact on aggregate unemployment, native- and foreign-born unemployment rates). We also find that migration is influenced by host economic conditions (migration responds positively to host GDP per capita and negatively to host total unemployment rate).
Keywords: E20; F22; J61; 330; immigration; growth; unemployment; panel VAR